1992
DOI: 10.1007/bf00058172
|View full text |Cite
|
Sign up to set email alerts
|

Breast carcinoma: periodicity in presentation of metastatic tumour growth in the axilla

Abstract: The clinical value of assessment of tumour load in the axilla in the treatment of breast cancer patients has stood the test of time. Much information is available on its extent and characteristic distribution but, in contrast, little is known of the biological factors that may control the timing of the metastatic phenomenon. There is recent circumstantial evidence that such factors may exist and this prompted the present detailed study of axillary metastases from a series of 437 consecutive cases of breast car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…16 Furthermore, it was found that the metastatic behavior of breast cancer can follow specific patterns, with periods of inactivity in which new tumor colonies in the axilla are not being seasonal variability of carcinomatous meningitis recruited. 8 It was also shown that the rate of micrometastases in the axillary lymph nodes was higher during the second half of the year. 9 Additionally, Mason et al demonstrated that the season the initial tumor was diagnosed was highly associated with the prognosis in breast cancer models.…”
Section: Discussionmentioning
confidence: 96%
“…16 Furthermore, it was found that the metastatic behavior of breast cancer can follow specific patterns, with periods of inactivity in which new tumor colonies in the axilla are not being seasonal variability of carcinomatous meningitis recruited. 8 It was also shown that the rate of micrometastases in the axillary lymph nodes was higher during the second half of the year. 9 Additionally, Mason et al demonstrated that the season the initial tumor was diagnosed was highly associated with the prognosis in breast cancer models.…”
Section: Discussionmentioning
confidence: 96%
“…For thyroid tumour diameter, there was a maximum period in the last months of the year between September and January, with a peak on December 8. In breast cancer, studies have shown that these tumours were also largest in the autumn (Hartveit et al, 1983;Hartveit, 1992). For thyroid tumour cell proliferation, maximal tumour growth was found in autumn and winter for both S-phase and G2M-phase fractions, and cosinor analysis indicated that the acrophases were located on September 28 for S-phase and November 3 for G2M-phase.…”
Section: Hospital Casesmentioning
confidence: 98%
“…The axilla provides a nodal 'site' in which tumour growth may be calibrated in different ways, allowing study of its progression in them. The presence of a yearly growth cycle in primary breast carcinoma has been reported from different parts of the world, including Norway [4][5][6][7][8][9][10][11], where it has also been related to nodal growth [12][13][14]. The present study concerns the numbers of cases presenting with different histological stages of nodal growth from breast carcinoma and the relation this bears to the yearly growth cycle of this metastatic tumour.…”
Section: Introductionmentioning
confidence: 99%